2022
DOI: 10.1002/star.202200022
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Industrial Applications of Natural and Hydrophobic Modified Starch

Abstract: This study presents a product based on natural cassava starch with hydrophobic characteristics, which has been developed to replace the natural starch used in different industries. The natural and hydrophobic starch results describe their characteristics, validate the hydrophobicity through mathematical modeling, and present case studies from the paper and fruit processing industries that will be compared. The hydrophobicity and low viscosity of the modified Starch studied in this paper result from the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[ 1,33 ] It has been reported that the hydrophobicity and low viscosity of modified starches used as biofilms in fruits extend their shelf life of fruits, preserving them for up to 65 days. [ 34 ] On the other hand, the swelling capacity was found to be higher for the starches modified by incorporation of acyl (8–88%) and acetyl (9–25%) groups, compared to that of the native starch (5–10%). Acylated starch at pH 10 exhibited a swelling capacity four times greater than that of native starch, possibly because the hydrocarbon molecules produce a structure with a greater number of pores, lower particle density, and greater porosity, which favor the entrapment of water molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,33 ] It has been reported that the hydrophobicity and low viscosity of modified starches used as biofilms in fruits extend their shelf life of fruits, preserving them for up to 65 days. [ 34 ] On the other hand, the swelling capacity was found to be higher for the starches modified by incorporation of acyl (8–88%) and acetyl (9–25%) groups, compared to that of the native starch (5–10%). Acylated starch at pH 10 exhibited a swelling capacity four times greater than that of native starch, possibly because the hydrocarbon molecules produce a structure with a greater number of pores, lower particle density, and greater porosity, which favor the entrapment of water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to those reported for films made with native starch [38] and coincide with the solubility tests for native chayote root starch, but they differ from the results reported by Colussi et al [1] This difference is possibly due to the nature and percentage of amylose and amylopectin or to the degree of substitution of the acetylated starch, and the granule sizes of the starches. [3,34] Tensile strength (TS), percent elongation at break (EB) and maximum tensile force (F max ) are important parameters that describe the mechanical properties of the films. Native starch films presented a F max (1.41-4.05 N), higher than that of films made with acetylated starch (0.70-1.10 N).…”
Section: Evaluation Of Films Made With Modified Starchesmentioning
confidence: 99%
“…The growth of consumption in domestic and foreign markets and the demand for higher quality constitute challenges for world production (Graciano et al, 2022;Rossi et al, 2024), especially in the food sector (Marques et al, 2021;Lermen et al, 2022;Matias et al, 2023). Generally, it is necessary to reduce external commodities with minimal environmental impacts in variable climatic conditions (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%